Reestruturação econômica e impacto regional: o novo mapa da indústria brasileira - Diniz, Clélio Campolina; Crocco, Marco Aurélio (Nova Economia, 2013)
Reestruturação econômica e impacto regional: o novo mapa da indústria brasileira